Pelatihan Pembelajaran Berbasis Game Online untuk Meningkatkan Penguasaan Kosakata Bahasa Inggris Bagi Siswa SMP Muhammadiyah Kota Jambi - Robi Soma; Yorina An'guna Bansa; Dana Amania; Ratih Rosita (Yayasan Literasi Sains Indonesia, 2024)
The purpose of this community service activity is to provide online game-based learning training to improve English vocabulary mastery for grade IX students of SMP Muhammadiyah in Jambi City. This online game training uses the Learning by Doing approach initiated by John Dewey. In the training attended by 19 students, they participated in learning provided by the PKM team which is a collaboration between lecturers from the University of Jambi (UNJA) and Muhammadiyah University (UM) in Jambi City. The training began with a presentation of material by the PKM team, namely by introducing various online games to students such as mobile legends, among us and so on and ended with a quiz with prizes. During the training process, the students looked active and enthusiastic using the gadgets provided by the PKM team. The game played was the mobile legend game considering that there were many words that they could learn and could be directly practiced in everyday English use, both spoken and written. Thus, through this PKM training activity, it is hoped that students will not only use online games as a game medium but more than that, namely as a medium for learning English, especially vocabulary.